CT CORRELATION WITH SEVERITY AND OUTCOME IN TRAUMATIC HEAD INJURY PATIENTS IN SAKONNAKHON HOSPITAL, THAILAND. - PRAMUALCHAROENKIYJ, Sudaphan (The ASEAN Journal of Radiology, 2023)
OBJECTIVE: To evaluate which features on the admission CT scan might add significantly to the neurologic status for predicting the outcome in patients with head injury. MATERIALS AND METHODS: 95 CT scans of patients with all grades of traumatic head injuries were retrospectively reviewed for roentgen findings on admission. Details from the CT scan on hemorrhage (type, number and size) and midline shift were correlated with neurologic status (assessed with Glasgow Coma Scale [GCS]) and patient outcome at discharge time (assessed with the Glasgow Outcome Scale [GOS]). RESULTS: GCS score was significantly lower in patients with subarachnoid hemorrhage, subdural, intracerebral hemorrhage, midline shift and associated primary brain injury. GCS changed as a function of hematoma size (P<.001) in the patient with focal hemorrhage. The presence of subarachnoid hemorrhage, subdural, intracerebral hematoma and midline shift were also significantly associated with poor outcome. Patients with normal CT scan were significantly more likely to have no or mild neurologic dysfunction and good outcome than those with intracranial hemorrhage (P<.001 ). CONCLUSION: CT findings, including type and number of intracranial hemorrhage, location, bleeding size, associated brain injury and midline shift have been the essential factors to predict the clinical outcome.